The complete mitochondrial genome of the silver chub, Macrhybopsis storeriana. Issue 1 (1st January 2016) - Gaughan, Sarah; Johnson, Robin; Wang, Jun; Wachholtz, Michael; Steffensen, Kirk; King, Timothy; Lu, Guoqing
Abstract: The complete mitochondrial genome of the silver chub M. storeriana was determined to be 16, 709 bp and contained 22 tRNA genes, 2 rRNA genes and one control region. The whole genome base composition was 30.3% A, 28% T, 25.5% C and 16.2 G. This complete mitochondrial genome provides essential molecular markers for resolving phylogeny and aiding future conservation efforts.